Islamic Education and Contemporary Challenges - Mustofa, Moh. Ayyub; Ramdhani, Fawaidur (Adabuna : Jurnal Pemikiran dan Pendidikan, 2023)
This research aims to find out and explain the problems faced by Islamic education, especially in the current contemporary era. To find out, researchers reviewed the philosophical framework of ontology, epistemology and also axiology. Based on research conducted by researchers, it is known that from an ontological perspective, Islamic education must strengthen its philosophical foundation, then from an epistemological perspective, it is necessary to improve learning practices in Islamic education, including developing dynamic-progressive curriculum policies and developing learning methods that relevant. Then finally, in terms of axiology, actors in Islamic education must have the will to produce and produce students who are competitive. So based on this, there needs to be awareness to build an Islamic education model with an integrative paradigm.